2019
DOI: 10.1186/s12199-019-0802-z
|View full text |Cite
|
Sign up to set email alerts
|

Di(2-ethylhexyl) phthalate-induced toxicity and peroxisome proliferator-activated receptor alpha: a review

Abstract: The plasticizer di(2-ethylhexyl) phthalate (DEHP) has been widely used in the manufacture of polyvinyl chloridecontaining products such as medical and consumer goods. Humans can easily be exposed to it because DEHP is ubiquitous in the environment. Recent research on the adverse effects of DEHP has focused on reproductive and developmental toxicity in rodents and/or humans. DEHP is a representative of the peroxisome proliferators. Therefore, peroxisome proliferator-activated receptor alpha (PPARα)-dependent pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 78 publications
0
41
0
Order By: Relevance
“…Of note, the embryonic lethality and the incidence of males observed following exposure to 100 μM DEHP are not as elevated as in null mutants in which key events for achieving accurate meiotic chromosome segregation, such as chromosome synapsis or recombination, are abrogated [37,38]. This may be due, at least in part, to inter-individual differences in the metabolism of DEHP, as previously observed in mice and humans [39].…”
Section: Environmentally-relevant Levels Of Dehp and Its Metabolites mentioning
confidence: 76%
“…Of note, the embryonic lethality and the incidence of males observed following exposure to 100 μM DEHP are not as elevated as in null mutants in which key events for achieving accurate meiotic chromosome segregation, such as chromosome synapsis or recombination, are abrogated [37,38]. This may be due, at least in part, to inter-individual differences in the metabolism of DEHP, as previously observed in mice and humans [39].…”
Section: Environmentally-relevant Levels Of Dehp and Its Metabolites mentioning
confidence: 76%
“…The geometric mean concentration of MEHP for bottlenose dolphins was significantly higher than NHANES concentrations [ 16 ]. MEHP is a metabolite of di-(2-ethylhexyl) phthalate (DEHP), which is primarily used to increase the flexibility of plastic (e.g., polyvinyl chloride, food packaging, wire covering, toys, medical tubing; [ 3 , 50 , 60 ]). DEHP can also be found in cosmetics, personal care products, oil and paint [ 3 ], although studies have suggested this is due to migration from the plastic containers housing these products [ 14 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEHP can also be found in cosmetics, personal care products, oil and paint [ 3 ], although studies have suggested this is due to migration from the plastic containers housing these products [ 14 , 61 ]. Because of weak bonds with the corresponding substrate, DEHP can be easily leached into food and the environment [ 3 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations